Analisis Pengaruh Ketidakseimbangan Beban dan Harmonisa Terhadap Arus Netral Pada Trafo Distribusi 8 Kapasitas 500 KVA di PPSDM Migas Cepu - Riki Khomarudin; Lukman Subekti (Jurnal Listrik, Instrumentasi, dan Elektronika Terapan, 2020)
Distribution transformer 8 at PPSDM Migas Cepu has a capacity of 500 kVA with load connected to boiler and refinery. The loading connected to the distribution transformer 8 is the majority of the 3-phase motor pump load and some 1-phase pump motors. In this case study measurements were made using the ampere pliers as the hypothesis of the current of each phase. From the measurement result there is imbalance of load between channel and also there is current value of neutral conductor side. And to know the content of harmonics on the distribution transformer, then measured with a power quality analyzer.The result of measurement with fluke quality 436 type fluke quality got result of measurement that current value at neutral conductor side equal to 14A. The value of load imbalance between conductor obtained by value of channel current R equal to 346A, in channel S equal to 306A, and in channel T equal to 318A. The THD value of the current obtained from the measurement with the power quality analyzer on the conductor side of R is 3.4%, on the conductor side S of 3.0%, and on the conductor side of T is 3.0%, and in the neutral channel is the greatest value of 29%. In the analysis of this chapter we get the result of imbalance loads of 4.6%, with the average loading of 45% of the total capacity of the transformer